2000
DOI: 10.1007/pl00008689
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of the replication origin and the telomeres of the large linear plasmid pSLA2-L in Streptomyces rochei

Abstract: The replication origin and both terminal segments were cloned from the large linear plasmid pSLA2-L in Streptomyces rochei 7434AN4. The basic replicon consists of a 1.9-kb DNA fragment, which contains the genetic information required for autonomous replication in circular form. Sequence analysis revealed two ORFs, RepL1 and RepL2, with no similarity to any of the replication initiator proteins in the database. Deletion and mutational analysis showed that RepL1 is essential for replication and RepL2 has a subsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…SCP1, SLP2, pSLA2, pSLA2-L, pSCL1, pSCL2, pRL2, pRL4, pFRL2 and pSHK1) commonly contain one internal replication origin (Shiffman & Cohen, 1992;Chang et al, 1996;Redenbach et al, 1999;Huang et al, 2003;Hiratsu et al, 2000;Wu et al, 2006;Xu et al, 2006a;Zhang et al, 2009). Recently, Zhang et al (2010) found that 54 kb pFRL1 contained two replication loci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCP1, SLP2, pSLA2, pSLA2-L, pSCL1, pSCL2, pRL2, pRL4, pFRL2 and pSHK1) commonly contain one internal replication origin (Shiffman & Cohen, 1992;Chang et al, 1996;Redenbach et al, 1999;Huang et al, 2003;Hiratsu et al, 2000;Wu et al, 2006;Xu et al, 2006a;Zhang et al, 2009). Recently, Zhang et al (2010) found that 54 kb pFRL1 contained two replication loci.…”
Section: Discussionmentioning
confidence: 99%
“…Artificially circularized SCP1 at 621-284 635 bp by an aac (3) , 1999;Huang et al, 2003;Xu et al, 2006a;Zhang et al, 2009), while rep (hypothetical protein)/non-coding sequences (ncs) have been identified in pSLA2-L, pSCL2, pRL2, pRL4 and pFRL2 (Hiratsu et al, 2000;Wu et al, 2006;Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Palindromes are important motifs that are involved in many cellular processes, such as DNA replication and gene regulation (Thukral et al, 1991;Hiratsu et al, 2000). To explore the change in palindrome abundance in pseudogenes during evolution, we compared palindrome abundances among the three pseudogene groups (see "MATERIALS AND METHODS" section) that differ in evolutionary distance.…”
Section: Evolution Of Palindrome Abundancementioning
confidence: 99%
“…The ooo autonomously replicating sequence of Streptomyces linear plasmids generally contains an origin of replication and one or more genes required for replication (24). These genes are located near the origin and may be subsidiary in some cases (25). Replication generates a 3' leading-strand overhang at the telomeres (Figure 1).…”
Section: Replication Of Linear Plasmidsmentioning
confidence: 99%